APPLICATION OF NANO- AND MICRO-MATERIALS IN WOOD-BASED COMPOSITES IN IRAN - R. Taghiyari, Hamid; Nadali, Elham; Arabi, Mahdi; Majidinajafabadi, Reza (Innovation in Woodworking Industry and Engineering design, 2024)
Wood is a renewable raw material in different kinds, patterns, strengths, and varieties that nature has provided to be used in a myriad of applications since before history. With the rapid increase in population on earth, and the consequent growing need for wood, fast-growing wood species became of more importance every day though their properties of these species are considered rather poor. However, they can satisfactorily be used in wood-based composite panels, like particleboard, medium-density fiberboard (MDF), high-density fiberboard (HDF), flakeboard, plywood, oriented strand lumber (OSL), and wood-plastic composites (WPCs). Still, production and application of composite panels have some troublesome drawbacks, including vulnerability to water and high humidity, and hot-press as a bottleneck in the production process as well. Over the past two decades or so, many studies were carried out to overcome these drawbacks and to improve properties in composite panels from different aspects, using different materials at nano- and micro-scales, mostly as resin reinforcement, additives, and cross-bonding agents. The present article tries to briefly provide an outlook on the strengths and weaknesses of some of the above mentioned materials that have been used in Iran, with an aim of giving an idea to young researchers for their future studies.